Absent ductus venosus: case series from two tertiary centres. (17th September 2018) - Maruotti, Giuseppe Maria; Saccone, Gabriele; Ciardulli, Andrea; Mazzarelli, Laura Letizia; Berghella, Vincenzo; Martinelli, Pasquale
Abstract: Introduction: Congenital absence of the ductus venosus (ADV) is a rare vascular anomaly often associated with fetal cardiac and extracardiac anomalies, aneuploidies, and hydrops. The prognosis depends on the patterns of abnormal venous circulation, on the associated malformations and on chromosomal aberrations. Methods: We performed a retrospective audit of all consecutive cases with ADV referred in our centres and analysed the outcomes. Results: A total of six cases with prenatally diagnosed ADV were identified. The gestational age at diagnosis ranged from 15 to 35 weeks. Karyotyping was performed in all cases. Normal karyotype was found in five out of the six cases. Overall, four neonates survived at 28 days follow-up. The other two died 48 h after delivery: both of them had extrahepatic ADV. Discussion: Absence of the ductus venosus may be compatible with normal fetal development without relevant disturbance of circulation and oxygenation independently from type of abnormal venous circulation.